LEGALISASI PERNIKAHAN MELALUI KONVERSI AGAMA: Di Desa Suwaru Kecamatan Gondanglegi Kabupaten Malang - Bahrul Ulum (LP3M IAI Al-Qolam Malang, 2018)
Suwaru is a village in Gondanglegi Malang with Christian and Islamic population, in which some people conduct interfaith marriages by carrying out religious conversions in advance for the sake of marriage legalization. This study focuses on the factors that cause religious conversion to legalize marriage to the people in this Village and examine the perspective of Islamic law on such religious conversion. The results showed that the factors causing religious conversion as a means of legalizing interfaith marriages are public ignorance of the religious law, pregnancy outside marriage, an influence of relations with religious traditions, economic factors, educational factors, administrative factors and love factors. As for interfaith marriages according to the perspective of Islamic law, there are actually three categories, namely; marriage between a Muslim man and a polytheist; marriage between a Muslim man and a woman of ahl al-kit?b; and the marriage between a Muslim woman and a non-Muslim man (musyrik or ahl al-kit?b). Whereas religious conversion is used to legalize interfaith marriages, which in Islamic law is also called h?lah (legal engineering), cannot be justified because it clearly violates existing provisions. Keywords: Religious Conversion, Marriage, Legalization, Suwaru